Petroleum geology of NW Europe : 50 years of learning : proceedings of the 8th Petroleum Geology Conference, held at the Queen Elizabeth II Conference Centre, London, 28-30 September 2015. (Published by the Geological Society, 2018)
The 8th Conference on the Petroleum Geology of NW Europe was held in September 2015 and marked the 50th anniversary of the first commercial discovery offshore in the North Sea (West Sole, in September 1965). Its focus was '50 Years of Learning - a Platform for Present Value and Future Success' and its objective was to provide an update on discoveries, developments, technologies and geological concepts from the region. The 39 extensively illustrated technical papers cover the full width of recent activity and are divided into the following sections: plays and fairways, play assessment, recent successes and learnings from failures, infrastructure-led exploration and development, late-life fields, re-development and the 'next life', and onshore exploration and development.